A novel training program: laparoscopic versus robotic-assisted low anterior resection for rectal cancer can be trained simultaneously - Wang, Yanlei; Wen, Dongpeng; Zhang, Cheng; Wang, Zhikai; Zhang, Jiancheng (Frontiers in Oncology, 2023)
Background: Current expectations are that surgeons should be technically proficient in minimally invasive low anterior resection (LAR)—both laparoscopic and robotic-assisted surgery, but methods of effectively training surgeons for both approaches are under-explored. We aimed to compare two different training programs for minimally invasive LAR, focusing on the learning curve and perioperative outcomes of two trainee surgeons. Methods: We reviewed 272 consecutive patients undergoing laparoscopic or robotic LAR by surgeons A and B, who were novice at conducting minimally invasive colorectal surgery. Surgeon A was trained by first performing 80 cases by laparoscopy and then 56 cases by robotic-assisted surgery. Surgeon B was trained by simultaneously performing 80 cases by laparoscopy and 56 robotic-assisted cases. The cumulative sum (CUSUM) method was used to evaluate the learning curves of operative time and surgical failure. Results: For laparoscopic surgery, the CUSUM plots showed a longer learning process for surgeon A than surgeon B (47 vs. 32 cases) for operative time, but a similar trend in surgical failure (23 vs. 19 cases). For robotic surgery, the plots of the two surgeons showed similar trends for both operative time (23 vs. 25 cases) and surgical failure (17 vs. 19 cases). Surgeon A and B learning curves were therefore divided into two phases at the 47th and 32nd cases for laparoscopic surgery, and the 23rd and 25th cases for robotic surgery. Clinicopathological outcomes of the two surgeons were similar in each phase of the learning curve for each surgery. Conclusions: Simultaneous training for laparoscopic and robotic-assisted LAR of rectal cancer is safe and effective, and is associated with accelerated learning curves.